MODEL STORYTELLING NARASI PARIWISATA REGENERATIF DI TAHURA NGURAH RAI PEMOGAN - Kardana, I Ketut; Sendra, I Made (Jurnal IPTA (Industri Perjalanan Wisata), 2025)
This study examines the regenerative tourism product storytelling model at Ngurah Rai Grand Forest Park (Tahura). Regenerative tourism focuses on environmental restoration, local community empowerment, and creating sustainable experiences that involve tourists. Through a storytelling approach, cultural values, history, and local wisdom narratives are used as key elements in designing unique and competitive tourism narrative products. The study uses a case study approach to deeply understand the social and ecological phenomena occurring at Tahura Ngurah Rai. Data collection techniques include interviews, observations, and literature reviews. The theory of historical commodification (G.J. Ashworth: 1999) serves as the main theory, supported by narrative theory (Gerard Genette, 1980) to design regenerative tourism product narratives based on storytelling. The findings show that the application of the storytelling concept in creating regenerative tourism narratives at Tahura Ngurah Rai not only enhances the economic value of tourism post-Covid-19 but also supports the regeneration of the mangrove ecosystem, community empowerment, and strengthens the image of tourist attractions based on local wisdom. This model provides strategic guidance for tourism managers in integrating sustainability, cultural, and local narrative elements as the foundation for developing tourism narrative products that have a positive ecological impact and gender empowerment.